Besarnya Impact Force pada Hammer Mill terhadap Kehalusan Pakan Ternak - Wahyu Perangin-Angin; Anna Angela Sitinjak (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
Along with the development of various types of industry, including an increase in food processing, there is also an increase in the demand for animal feed. In the processing of animal feed using a machine that can grind is called a hammer mill using the principle of impact force. The purpose of this study was to find out how impact force influences the fineness of animal feed. The research method used is descriptive research, where this research begins by calculating the amount of impact force that occurred in a hammer mill in a factory, then sample is taken after being ground in a hammer mill and the fineness level is calculated using mesh 16 and mesh 40. Animal feed samples used are about  corn 40-50%, soybean meal 18-38%, coconut meal 15%, fine bran 10-20%, fish meal 4-11%, limestone meal as a source of calcium. as much as 2-5%, and various vitamins and minerals. The results of this study indicate that with an impact force of 32,536,680 N, the fineness level on mesh 16 is 99.54% and on mesh 40 is 88.46%. This research is expected to be useful as a reference for further research related to the impact force associated with rpm variations in seeing the best feed quality.